TFA and the magical thinking of the "best and the brightest" - Megan Blumenreich; Bethany Rogers (Arizona State University, 2016)
This article draws on oral history testimonies to examine the experiences of participants in the inaugural 1990 cohort of Teach For America (TFA)-a group of young people dubbed the "best and brightest" of their generation and tasked with "saving" urban education. For 25 years, TFA has operated according to the principle of the "best and brightest," in which it is assumed that participants' personal qualities and prior academic achievement can stand in for deep professional knowledge and experience. Yet as our data show, the presumptions-that any "smart" person should be able to pick up teaching by doing it, that there is no specialized knowledge needed in order to teach, and that "outsiders" with little knowledge of a school community and its families can "swoop in" and "rescue" underserved students-ultimately set up and demoralized the participants with whom we spoke when they could not live up to such unrealistic expectations.  Through participants' words and experiences, framed in historical context, we raise questions about the myth of the "best and brightest," the theory of action promoted by TFA, and what it takes to teach in urban classrooms.